(untitled) (Research, Society and Development, 2019)
Introduction: Congenital syphilis is a serious public health problem and it is questioned whether an educational technology can be used in its prevention. Objective: To construct and validate an educational technology (video) on the subject of Congenital Syphilis. Method: This is a methodological research of the type development, carried out between December 2017 and November 2018. The analysis and validation of content occurred through the Delphi Technique, with participation of ten specialists in the health area, in the first cycle and nine, in the second. For validation of the video by the experts, the script items presented Content Validity Index greater than or equal to 0.78. Results: Following the validation of the script, the video was filmed through technical support of two journalism professionals. After the production of the educational material (video), it will be made available online so that it can be used by health professionals, academics and users interested in the subject. Conclusion: Educational video can be an ally in the prevention of congenital syphilis diseases and in the promotion of maternal and child health, being an important tool in care.